Palaeopathology of human remains of the 1st century BC–3rd century AD from Armenia (Beniamin, Shirakavan I) - Khudaverdyan, Anahit Yu. (Anthropological Review, 2015)
The aim of this article was to document the pathology of the individuals from the archeological sites of Beniamin and Shirakavan I, Armenia, dated on the 1st century BC - 3rd century AD. The findings revealed that two groups differed in mean age at death of adults. At Beniamin it was 24 years, 40.8 years for males and 30.9 years for females, whereas at Shirakavanit it was 29.3 years, 29.6 years for males and 35.8 years for females. The greatest mortality appeared to have occurred when the children reached the age of one year (Beniamin). The population had high number of young-adult females with a cause of death associated with child-bearing . Very few females survived to old age. Traumatic conditions (63.64%) and enamel hypoplasias (57.2%) have a high frequency in the skeletal material from Shirakavan. The volume of selection of Shirakavan does not allow itself to so big discussion as it was possible with the Beniamin site. Fewer hypoplasias in Beniamin group indicate that food resources were more abundant and more easily exploited. The small frequency of a periodontal disorder indicates that dental hygiene was good during the Antiquity period. We here report a case of possible pituitary dwarfism and a case of decapitation.